Isolated Breast Relapse of Early T-Cell Precursor Acute Lymphoblastic Leukemia after Stem Cell Transplantation: A Pediatric Case and Literature Review - Bo Ram Kim; Hee Jo Baek; Yoon Jung Choi; Yun Young Lee; Joheon Kim; Hoon Kook (The Korean Society of Pediatric Hematology-Oncology, 2022)
Extramedullary relapse in acute lymphoblastic leukemia (ALL) usually occurs in the central nervous system and testes those are known as sanctuary sites. Only a few cases of isolated breast relapse after allogeneic hematopoietic stem cell transplantation (HSCT) have been reported in pediatric ALL, with little known about the optimal treatment and prognosis of such cases. Herein, we report a pediatric case of isolated breast relapse with early T-cell precursor ALL after HSCT. We also describe a literature review of six pediatric cases, including our case.